The Effect Of Intellectual Intelligence And Emotional Intelligence On Competence And Employees Performances - Darman Darman; Wahyu Maulid Adha (Jurnal Manajemen, 2022)
This study aims to test the relationship and influence between intellectual intelligence and emotional intelligence towards competency and performance and partially test both variables. The object of this study was a civil servant at the Gorontalo Regency Regional Secretariat Office with a sample of 150 respondents by spreading questionnaires online. This study also uses the structural equation technique with data analysis using SEM-PLS. The results showed that intellectual intelligence variables positively and significantly influence employees' competence and performance. On the other hand, emotional intelligence does not have a significant effect on employee performance. This research can reference relevant agencies in looking at the relationship between intellectual intelligence and emotional intelligence to employees' competence and performance to take the right policies. This research in the design is static. The model that we developed based on empirical studies and testing is limited to establishing simple relationships related to intellectual intelligence and emotional intelligence variables that can affect employees' competence and performance.